(5w+1)(2-w)=0

Simple and best practice solution for (5w+1)(2-w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5w+1)(2-w)=0 equation:


Simplifying
(5w + 1)(2 + -1w) = 0

Reorder the terms:
(1 + 5w)(2 + -1w) = 0

Multiply (1 + 5w) * (2 + -1w)
(1(2 + -1w) + 5w * (2 + -1w)) = 0
((2 * 1 + -1w * 1) + 5w * (2 + -1w)) = 0
((2 + -1w) + 5w * (2 + -1w)) = 0
(2 + -1w + (2 * 5w + -1w * 5w)) = 0
(2 + -1w + (10w + -5w2)) = 0

Combine like terms: -1w + 10w = 9w
(2 + 9w + -5w2) = 0

Solving
2 + 9w + -5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(2 + -1w)(1 + 5w) = 0

Subproblem 1

Set the factor '(2 + -1w)' equal to zero and attempt to solve: Simplifying 2 + -1w = 0 Solving 2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1w = 0 + -2 -1w = 0 + -2 Combine like terms: 0 + -2 = -2 -1w = -2 Divide each side by '-1'. w = 2 Simplifying w = 2

Subproblem 2

Set the factor '(1 + 5w)' equal to zero and attempt to solve: Simplifying 1 + 5w = 0 Solving 1 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5w = 0 + -1 5w = 0 + -1 Combine like terms: 0 + -1 = -1 5w = -1 Divide each side by '5'. w = -0.2 Simplifying w = -0.2

Solution

w = {2, -0.2}

See similar equations:

| (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) | | 80+5x=7x | | 4(5r-5)=-20-7r |

Equations solver categories